L1 Derivational Morphology: Patterns And Implications for English Language Teaching - Herayati, Herayati; Wilymafidini, Okti; Musdizal, Musdizal (Universitas Muhammadiyah Barru, 2025)
Derivational morphological process is one of the teaching materials in Morphology course in English Department of IAIN Kerinci. Then, based on the English Department curriculum, it is required to integrate local wisdom in teaching English areas,. Thus, Bahasa Kerinci derivational morphological process is an essential part of research since the data obtained will provide the derivational morphological process, its patterns, and the implications for English language teaching as well. This research is descriptive qualitative research. The lists of vocabularies in Bahasa Kerinci were the data of this research. Then, the lecturers of English department of IAIN Kerinci were interviewed in term of the implications of the patterns of words which are formed based on derivational morphological process. Based on data collected, it was found that the derivational word formation processes in Bahasa Kerinci were found in some categories, the patterns of derivational word formation processes in Bahasa Kerinci were found by adding prefixes, for example, prefix ng- + base becomes ngendoh which has meaning make become shorter and prefix ba- + penyap becomes bapenyap which has meaning sweep floor. Additionally, the implications of Bahasa Kerinci derivational word formation process to English language teaching in English Department of IAIN Kerinci were found in the case of reading course and linguistics courses. In this case, by having good understanding of derivational morphological process, they can enrich their vocabulariesthat can give good impacts for them to comprehend reading texts easily and they can also have good understanding of word – formation process. Therefore, it is suggested to English Education department students to have good awareness and understanding of their L1 derivational morphological process because it provides good impacts to their English language skills and learning.